Toxicity of Large and Small Surface-Engineered Upconverting Nanoparticles for In Vitro and In Vivo Bioapplications - Machová Urdzíková, Lucia; Mareková, Dana; Vasylyshyn, Taras; Matouš, Petr; Patsula, Vitalii; Oleksa, Viktoriia; Shapoval, Oleksandr; Vosmanská, Magda; Liebl, David; Benda, Aleš; Herynek, Vít; Horák, Daniel; et al. (International journal of molecular sciences, 2024)
In this study, spherical or hexagonal NaYF4:Yb,Er nanoparticles (UCNPs) with sizes of 25 nm (S-UCNPs) and 120 nm (L-UCNPs) were synthesized by high-temperature coprecipitation and subsequently modified with three kinds of polymers. These included poly(ethylene glycol) (PEG) and poly(N,N-dimethylacrylamide-co-2-aminoethylacrylamide) [P(DMA-AEA)] terminated with an alendronate anchoring group, and poly(methyl vinyl ether-co-maleic acid) (PMVEMA). The internalization of nanoparticles by rat mesenchymal stem cells (rMSCs) and C6 cancer cells (rat glial tumor cell line) was visualized by electron microscopy and the cytotoxicity of the UCNPs and their leaches was measured by the real-time proliferation assay. The comet assay was used to determine the oxidative damage of the UCNPs. An in vivo study on mice determined the elimination route and potential accumulation of UCNPs in the body. The results showed that the L- and S-UCNPs were internalized into cells in the lumen of endosomes. The proliferation assay revealed that the L-UCNPs were less toxic than S-UCNPs. The viability of rMSCs incubated with particles decreased in the order S-UCNP@Ale-(PDMA-AEA) > S-UCNP@Ale-PEG > S-UCNPs > S-UCNP@PMVEMA. Similar results were obtained in C6 cells. The oxidative damage measured by the comet assay showed that neat L-UCNPs caused more oxidative damage to rMSCs than all coated UCNPs while no difference was observed in C6 cells. An in vivo study indicated that L-UCNPs were eliminated from the body via the hepatobiliary route; L-UCNP@Ale-PEG particles were almost eliminated from the liver 96 h after intravenous application. Pilot fluorescence imaging confirmed the limited in vivo detection capabilities of the nanoparticles.
Keywords: Cell Survival; Oxidative Stress; Nanoparticles; oxidační stres; viabilita buněk; krysa rodu Rattus; zvířata; toxicity; myši; Polyethylene Glycols; velikost částic; Mice; Male; mezenchymální kmenové buňky; nanočástice; upconverting nanoparticles; nádorové buněčné linie; Rats; Animals; Cell Line, Tumor; polyethylenglykoly; mužské pohlaví; Particle Size; Mesenchymal Stem Cells; biological applications